Factors Affecting Gen Z Purchase Decisions on Shopee (Case Study in Surakarta City) - Yanuarisa, Agiardo; Wijiastuti, Sri; Dwanita Widodo, Zandra (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to determine the influence of information quality, electronic word of mouth (e-WOM), and ease of use on purchase decisions among Generation Z in Surakarta City, utilizing the Shopee e-commerce platform. The research employed a quantitative approach with primary data collectedthrough a survey involving 100 respondents. Multiple linear regression was used to analyze the data. The results showed that: information quality has a significant positive effect on purchase decisions (sig. = 0.013), e-WOM has a significant positive effect on purchase decisions (sig. = 0.003), and ease of use has a significant positive effect on purchase decisions (sig. 0.013). Simultaneously, information quality, e-WOM, and ease of use significantly influence purchase decisions (sig. 0.000). The determination coefficient (R²) of 37.9% indicates that the regression model can explain the purchase decision variable, while 62.1% is explained by other variables outside this study. The Adjusted R² value of 0.360 indicates the model's suitability after adjustment for the number of independent variables and sample size. These findings suggest that Shopee should prioritize improving the quality of information, leveraging credible e-WOM reviews, and enhancing user interfaces to effectively support consumer purchase decisions.